2022
DOI: 10.1186/s12870-022-03543-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and metabolic traits of some Egyptian species of Cassia L. and Senna Mill (Fabaceae-Caesalpinioideae)

Abstract: The genus Cassia and Senna have been classified under subfamily Caesalpinioideae of family Fabaceae (Leguminosae) of order Fabales. There is a scarce taxonomical studies of the genus Cassia and Senna inhabiting Egyptian environments, thus, the main objective of the current was to revise and authenticate the phylogenetic relationship between studied taxa of the species of the genera Cassia and Senna in Egypt using the recent tools of ITS barcoding, RAPD analysis and metabolic profiling, in comparing to the trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…In our previous study on the ITS region of species of Cassia and Senna, it was found that the average size of the ITS region varied from 403 to 796 bp, while the detected nucleotide frequencies were 20.86% (A), 18.83% (T/U), 29.65% (C), and 30.67% (G). On the intergenic spacer ITS sequences, transitions were more common than transversions (Eldemerdash et al, 2022). However, older studies have proposed that the size of the ITS region in angiosperms ranges from 565 to 700 bp (Liston et al, 1996).…”
Section: Length Variation Gc Content Nucleotide Composition and Mutat...mentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study on the ITS region of species of Cassia and Senna, it was found that the average size of the ITS region varied from 403 to 796 bp, while the detected nucleotide frequencies were 20.86% (A), 18.83% (T/U), 29.65% (C), and 30.67% (G). On the intergenic spacer ITS sequences, transitions were more common than transversions (Eldemerdash et al, 2022). However, older studies have proposed that the size of the ITS region in angiosperms ranges from 565 to 700 bp (Liston et al, 1996).…”
Section: Length Variation Gc Content Nucleotide Composition and Mutat...mentioning
confidence: 99%
“…Metabolic profiling of the studied plants was conducted as a marker for authentication of the traditional taxonomic features and DNA barcoding analysis (Eldemerdash et al, 2022). Estimation of volatile chemical compounds by GC-MS for plant differentiation has been recognized as one of the key technological tools for metabolic profiling and taxonomic analysis that can be used to confirm traditional taxonomic features.…”
Section: Gc-ms Metabolic Profiling Analysismentioning
confidence: 99%
See 3 more Smart Citations